Diseño del sistema de gestión de seguridad y salud en el trabajo según la NTC OHSAS 18001:2007 de la empresa Geotopo.cons LTDA (2014)
This degree paper was done with the aim to design an occupational health and safety management system in the company GEOTOPO.CONS, using the specifications OHSAS 18001, in order to minimize the risks to which the employees are exposed day after day, to contribute with the well-being of them and to increase the productivity of the company. The first stage was to create a process map in order to know the strategic guidelines of the company, and to align them with system designed The second stage was to make two diagnosis; the first one was of the current situation of the company comparing it against the requirements demanded by the specification OHSAS 18001, the second one, evaluated the fulfillment of the legal Colombian regulations by the company. The third stage, was to established the corrective and preventive measures and plans of action to fit the situation of the company according to the requirements demanded by the Colombian Law and the specifications OHSAS 18001. It also was developed a risks map to analyse the vulnerability of the company and a plan of implementation for the system to be use by the company. Finally the financial analysis was done in order to know if the implementation of the system was feasible for the company or not.